UKURAN PERUSAHAAN, PROFITABILITAS, UMUR PERUSAHAAN, SOLVABILITAS DAN UKURAN KAP TERHADAP AUDIT REPORT LAG - Ika Destriana Widiastuti; Andi Kartika (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
Audit report lag is time in finishing job audient until publication date of audit report. This study aims to examine and analyze the effect of the size of the company , profitability, age of the firm , solvency , size of public accounting firms to audit report lag on manufacturing companies listed in Indonesia Stock Exchange (BEI). The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2013 to 2016 that reported complete financial statements and published in Indonesian Capital Market Directory (ICMD) and IDX website. Samples are included in the criteria of this study were 45 companies using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis using SPSS 20. The results showed that the variable of the size of the company are significant positive effect on audit report lag, variable solvency are not significant positive effect on audit report lag. variable, the size of the company and profitability are significant negative effect on audit report lag, and variable age of the firm is not significant negative effect on audit report lag. Keywords: audit report lag the size of the company, profitability, the age of the company, solvency, the size of the public accounting firm (KAP).